Effect of career development intervention module on unskilled vehicle assembly workers’ career competencies - Adanan, Mona Adlina (2020)
There is a need for career development intervention for working adults, especially those entering the workforce without post-secondary education. Based on this need, this research aimed to develop a Career Development Intervention Module (CDIM) based on the Intelligent Career Model (ICM), and to examine its effect on the career competencies of unskilled workers in Malaysia. This research has two parts. The first describes the development of the CDIM, and the second reports a true experimental study to test the effectiveness of the CDIM on the career competencies of unskilled vehicle assembly workers. The CDIM was developed based on the Sidek Module Development Model (SMDM) and, to examine its validation and reliability, a descriptive study was used. The experimental research design was used on randomised pre-test, post-test, followup and control groups to determine the effectiveness of the CDIM. The subjects of this study were selected from 328 production workers at a vehicle assembly plant who met the criteria of unskilled workers set for this study. Sixty subjects were selected and assigned to two groups, the Experimental Group (EG) (n= 30) and the Control Group (CG) (n=30). The EG subjects were given treatment using the CDIM over four sessions conducted weekly, with each session taking four hours to complete. In total, 16 hours were needed to complete the CDIM. In this study, career competencies were measured using a questionnaire. Its subscales were knowing-why, knowing-whom and knowing-how. Data were analysed using descriptive statistics, one-way MANOVA and repeated measures MANOVA, at significance level of .05. The content validity coefficient for the CDIM developed was .90 and its Alpha Cronbach value of reliability from the pilot study was .98. This showed that the CDIM was suitable to be conducted with the unskilled workers to increase their career competencies. A comparative analysis between the EG and CG indicated that, for unskilled workers, a four-week career development intervention module produced significantly higher levels of career competencies and the sub-scales of knowing-why, knowing-whom and knowing-how, compared to the group who did not receive the intervention. Furthermore, the results of repeated-measures MANOVA showed that the CDIM was effective in increasing the levels of career competencies and the sub-scales of knowing-why, knowing-whom and knowing-how within the EG during the posttest. The sustainability of the increased career competencies was also proven in the follow-up test. This study has implications for organisations with unskilled workers and those working on the career development of employees. Furthermore, the career counsellor at an organisation may apply the CDIM in their organisation, especially in developing employee career competencies. This study also contributed to the efforts to expand the ICM application, especially in enhancing career development intervention.